2022
DOI: 10.55230/mabjournal.v51i1.2201
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR PCR ASSAYS FOR DETECTION OF Ganoderma PATHOGENIC TO OIL PALM IN MALAYSIA

Abstract: Ganoderma boninense is a fungal pathogen that causes basal stem rot (BSR) disease in oil palm. Being a serious disease problem to the oil palm industry, monitoring and detecting the pathogen is of the utmost importance to reduce disease spread and facilitate effective management strategies. Because traditional culture-based assay is time-consuming, labour-intensive and required special skills in mycology, plant pathologists are turning to more accurate, sensitive and fast methods such as molecular techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They showed higher sensitivity and speed than conventional methods, successfully detecting the pathogen in inoculated plantlets. This offers promising prospects for effective disease control [ 164 ].…”
Section: Research On Detection Methods For Basal Stem Rotmentioning
confidence: 99%
“…They showed higher sensitivity and speed than conventional methods, successfully detecting the pathogen in inoculated plantlets. This offers promising prospects for effective disease control [ 164 ].…”
Section: Research On Detection Methods For Basal Stem Rotmentioning
confidence: 99%
“…Out of these 320 kb fragments of GanET-ITS3 was very crucial for identification of infection [51]. Similarly, a study developed Real-time PCR using primers GB4F (5′-CGTTCGTTTGACGAG TTTGC-3′) and reverse GB4R (5′-GGTTGGTTTCTTT TCCT-3′), designed based on specific sequence data for the ITS region universal fungal primer pair ITS1 and ITS4 for rapid detection of pathogenic Ganoderma species to oil palms of Malaysia [54]. A number of other studies [54,[55][56][57] have developed similar type of protocols for rapid identification of Ganoderma infection in oil palms but no study has been found to detect G. lucidum infection in D. sissoo, S. catechu, and other forest species and hence researchers are expected to focus in this virtue.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Besides, disease conquest by fungal control agents has been found equivalent to the chemical counterparts Sundram et al, 2022). Fungicides such as hexaconazole are effective in treating upper and basal stem rot Ganoderma diseases in oil palm (Nur-Rashyeda et al, 2022). The infected palms continue to survive and actively produce fruit bunches.…”
Section: P R E S Smentioning
confidence: 99%